The high expression of lncRNA TUG1 correlates with progressive tumor condition and less satisfying survival profiles in prostate cancer patients - Yu, Jiajun; Wang, Yong; Peng, Song (Translational Cancer Research, 2019)
Background: This study aimed to evaluate the correlation of long noncoding RNA taurine-upregulated 1 gene (lncRNA TUG1) with tumor characteristics and survival in prostate cancer patients, and the effect of lncRNA TUG1 on proliferation and apoptosis in prostate cancer cells. Methods: Two-hundred and eight prostate cancer patients who underwent tumor resection were continuously reviewed in this study. Tumor tissue and paired adjacent tissue were obtained and polymerase chain reaction assay was performed to detect the expression of lncRNA TUG1 in tumor tissue. PANC-1 cells were obtained and transferred with blank mimic, lncRNA TUG1 mimic, blank inhibitor, and lncRNA TUG1 inhibitor plasmids, then cell proliferation was detected by CCK-8, and cell apoptosis was evaluated by AV/PI assay. Results: LncRNA TUG1 expression was elevated in tumor tissue compared with paired adjacent tissue (P